Dispersion-free characterization of terahertz slab–waveguide modal confinement based on a metal Bragg grating structure - Borwen You; Che-Chu Hsieh; Ryuji Iwasa; Hung-Yi Tsai; Yen-Shan Lin; Liang-Cheng Yu; Pin-Jung Lu; Shiun-Yun Chang; Yuan-Chi Wu (Results in Physics)
Photonic waveguide structures that use periodic metal grooves and periodically perforated metal slits (PPMSs) can laterally confine Sommerfeld and Zenneck surface waves of metals with the electric field accumulation among metal interspaces in the terahertz (THz) region, instead of the total internal reflection principle of dielectric slab media. For the efficiency enhancements of THz-wave coupling and slab–waveguide confinement, specific integrators with high refractive indices or specified for input angles of transverse magnetic polarized waves, such as prisms, metal blades, and waveguides, are requested to excite spoof surface plasmons in the THz region. However, the integrator-assembled slab–waveguides encounter challenges of THz pulse-wave communication in compact and low-distortion systems. A resonant waveguide grating structure based on PPMSs is experimentally demonstrated to confine THz lateral waves from the plane-wave radiation in free space. The open frame and periodic metal cavities of PPMSs can work as a slab–waveguide to transmit structural confined waveguide modes with forwarding evanescent waves of Fabry–Pérot resonance. For 0.1–1 THz waves, the short wavelengths that are both less than half the metal slit width and 3.75 times the metal thickness can lead to zero dispersion and the highest confinement factor in a slab–waveguide for PPMS-confined THz waves. This behavior is opposite to the high structural dispersion in confined THz waves of surface plasmonic devices.